Impact of Role Conflict on the Creativity of Software Project Managers in Nepal: Does Area of Specialization Influence their Creativity? - Ojha, Gaurav (SXC Journal, 2026)
Recognizing role conflict as a multidimensional construct, this study investigates to what extent different dimensions of role conflict impacts creativity of project managers in the context of software development firms in Nepal. A cross-sectional survey research design has been used in this study to assess the relationships between intra-sender, inter-role, intra-role, and cross-functional role conflicts, and the creativity of software project managers. The results of this study show intra-sender conflict has a detrimental effect on creativity of software project managers, whereas cross-functional role conflict has a favorable and significant impact. This study also finds that that area of specialization of project manager doesn’t influence how these managers evaluate their levels of creative. Based on findings this study recommends software development companies to enhance positive team culture and facilitate environment of open dialogue allows the project managers to transform their experiences of role conflict into creativity.